A PRAGMATIC ANALYSIS OF THE DIRECTIVE UTTERANCES IN THE PERCY JACKSON AND THE OLYMPIANS NOVEL AND ITS TRANSLATION - Wibowo, Furqon Edi (English Education: Jurnal Tadris Bahasa Inggris, 2018)
The aims of this study were to describe the varieties of the language form of directive utterances and to examine the equivalences of the speaker’s intention of directive utterances in the novel of Percy Jackson and the Olympians and its translation.. The method applied was descriptive qualitative with the data in the form of the directive utterances in the novel of Percy Jackson and the Olympians and its translation.The result of the study shows that first, the language form of directive utterances used in the original novel and its translation are not always appropriate. The language form includes the variation from declarative in the source language turn into imperative in its translation, interrogative in the source languge turn into imperative in its translation and imperative in the source language turn into declarative in its translation. Second, the translation based on speaker’s intention is equivalent because from 44 sentences in data, there are only 6 (13,6 %) data that are unequivalent. It means that there are 38 data (86,4 %) which are equivalent based on speaker’s intention.Key words : pragmatic, directive utterances, translation